Malaysia Economic Monitor, June 2013 : Harnessing Natural Resources - World Bank (Washington, DC, 2014)
Following a strong performance in 2012, Malaysia's economy hit a soft patch in the first quarter of 2013. Economic growth has been supported by the strong, broad-based performance of domestic consumption and investment from public and private sources. The acceleration of investment growth has been a key feature of the recent growth trend. Public and private consumption has also underpinned growth. Accommodative fiscal and monetary policies have supported both higher (real) household incomes and sustained credit growth, which along with firm labor markets provided a solid backdrop for consumption growth even as agricultural commodity prices declined. Despite significant expenditure overruns, the government met its fiscal deficit target for 2012. Supply-side factors kept inflation subdued amidst robust domestic demand. Monetary authorities emphasized macro-prudential regulation as the policy interest rate continued to be pulled in two directions. Malaysia is likely to continue posting solid growth rates in 2013 and 2014. Growth in 2013 is projected to come at 5.1 percent, supported by the strong momentum in investment growth, still-accommodative fiscal and monetary policies, higher household income due to tight labor markets, and modest improvement in the export sector. The sustainability of Malaysia's favorable near-term prospects into 2015 and beyond continues to hinge on the implementation of structural reforms. Having a rigorous investigation of the effectiveness of various tax incentives across different industries, and comparing the benefits with the costs in foregone revenues, will provide important lessons, to Malaysia and other countries, of the appropriate role for fiscal incentives in horizontal diversification.